Recent advances in the functional explorations of nuclear microRNAs - Hu, Xiaozhu; Yin, Guoquan; Zhang, Yuan; Zhu, Liangyu; Huang, Haoyu; Lv, Kun (Frontiers in Immunology, 2023)
MicroRNAs (miRNAs) are a class of about 22 nucleotide non-coding small RNAs, which play a momentous role in a range of biological processes and diseases. It is generally accepted that miRNAs mainly locate in the cytoplasm and function as the post-transcriptional regulators. The classic regulatory manner of miRNA is the post-transcriptional gene silencing that miRNA assembles the miRNA-induced silencing complex (miRISC) to degrade the target mRNAs or suppress their translation by the seed sequence at the 5’ end. However, in recent years, plenty of studies have shown that mature miRNAs also exist in the nucleus and mediate the transcriptional gene activation or silencing in both animal and plant cells, which broadens the functional spectrum of miRNAs. In this study, we reviewed studies of nuclear miRNAs functions in order to map the regulatory network of nuclear miRNAs.